Problemy logistyki w gospodarce lokalnej - Kowalczyk, Lucjan (Logistic Problems in Local Economy, 2006)
A comprehensive approach to local economy involves opening the doors to the possible applications of logistics concepts oriented towards optimising the advantages of a local system. The paper presents the scope of logistics relevant to local economies and discusses the factors that 1) enhance the input-output processes within the technical infrastructure, 2) indicate the possibilities (opportunities and perspectives) of applying logistics concepts in local economies, and also suggests the research and teaching subjects that could make the basis for practical orientation of logistics in local economies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 302-316